High prevalence of familial and genetic disease in children with cardiomyopathies: baseline paediatric data from the ESC EORP Cardiomyopathy and Myocarditis registry. (25th November 2020) - Kaski, J.P; Maggioni, A.G; Charron, P; Elliott, P.M; Gimeno, J.R; Laroche, C; Tavazzi, L; Tendera, M; Caforio, A
Abstract: Background: Previous studies on paediatric cardiomyopathies have provided useful information on their epidemiology and clinical presentation but have been limited by a lack of detailed data on genetic testing and aetiology. Purpose: The purpose of this study was to examine the frequency of familial and genetic disease among children with cardiomyopathy enrolled in the European Society of Cardiology (ESC) Cardiomyopathy and Myocarditis EORP Long-Term Registry (CMY-LT). Methods: 633 individuals aged <18 years with hypertrophic cardiomyopathy [HCM; n=387 (61%)], dilated cardiomyopathy (DCM; n=205 (33%)], restrictive cardiomyopathy [RCM; n=28 (4%)] and arrhythmogenic right ventricular cardiomyopathy [ARVC; n=11 (2%)] were enrolled by 26 centres from 14 countries. Mean age at diagnosis was 5.2 (±5.4) years and there was a male predominance [n=372 (59%)] across all cardiomyopathy subtypes, with the exception of DCM in those diagnosed <10 years of age (p=0.005). 541 (87%) were probands compared to 83 (13%) first-degree relatives. Results: Overall, 253 patients (47% of those reported) had familial disease; in those diagnosed between 10 and 18 years of age, familial disease was most frequent in HCM and least frequent in DCM [57 (55%) vs 12 (32%); p=0.046]. Genetic testing was performed in 414 (68%) patients. In those diagnosed <10 years, genetic testing was more frequently performed in HCM [128 (67%) vs 33 (37%) in DCM, 10 (56%) in RCM and 1 (50%) in ARVC; p=0.008]; in those aged 10–18, genetic testing was most frequent in ARVC [n=8 (89%)] followed by HCM [n=81 (69%)], RCM [n=1 (50%)] and DCM [n=22 (46%); p=0.007]. A causative mutation was reported in 250 patients (60%), with a higher yield in those aged 10–18 vs <10 years [77 (69%) vs 172 (57%), p=0.032]. In those <10 years, the prevalence of reported causative mutations was highest in HCM [128 (67%) vs 10 (56%) in RCM, 1 (50%) in ARVC and 33 (37%) in DCM; p<0.001]; in those 10–18 years, there was no significant difference in prevalence of reported causative variants between cardiomyopathy subtypes. Rare disease phenocopies were reported in 171 patients (27%): malformation syndromes [n=75 (12%)]; neuromuscular disorders [n=49 (8%)]; inborn errors of metabolism [n=20 (3%)]; mitochondrial [n=18 (3%)]; and chromosomal [n=15 (2%)]. Phenocopies were reported most frequently in patients <10 years [135 (30%) vs 35 (20%) in those aged 10–18 years; p=0.008], particularly in HCM in those <10 years [n=110 (41%); p<0.001 vs other subtypes] and DCM in those aged 10–18 years [n=18 (38%); p=0.03 vs other subtypes]. Conclusion: This study confirms the heterogeneous aetiology of childhood cardiomyopathies and demonstrate a higher prevalence of familial disease than previously reported in paediatric populations. Genetic testing is performed in a high proportion of patients, with a high yield of reported causative variants. Funding Acknowledgement: Type of funding source: None